INTEGRATED RADIO SCANNING AND COMMUNICATION SYSTEM - VASYLKIVSKYI, MYKOLA; HORODETSKA, OKSANA; STALCHENKO, OLEXANDER; BUDASH, MYHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article discusses ways to optimize the performance of information communication systems, which includes increasing spectral efficiency and reliability while minimizing delay and energy consumption due to the full integration of communication and scanning services. The functioning algorithm of the integrated scanning and communication system and the organization scheme of the communication mode using the scanning process based on the proposed generalized model of the integrated scanning and data transmission system are considered.Ways to improve the efficiency of telecommunication systems due to the joint use of communication and scanning tools with the best compromise between scanning characteristics and the bandwidth of the transmission channel are considered.Peculiarities of improving wireless communication systems with regard to high data transfer rates, low latency and wide connection possibilities are studied. In particular, access to other system functions, such as scanning/visualization and localization, is justified. Due to the considered innovative applications, the possibility of increasing the performance of the integrated wireless scanning and communication system (ISAC) is determined. The researched positioning process in 5G is proposed to be expanded due to additional detection functions, in particular with the use of new metrics such as accuracy and resolution. New KPIs in 6G networks are considered, replacing the KPI of positioning accuracy in 5G. As a result, key performance indicators based on different application scenarios are proposed, the accuracy of which should be from 1 to 10 cm, and the resolution should be up to 1 mm.The potential of the new ISAC technology was investigated, in particular, the features of the coexistence of communication and scanning modules in an integrated solution at the system level and methods of increasing the efficiency of coexistence at the system level were considered; justification of a positive result from an integrated system solution for communication and scanning services; advantages and disadvantages of existing communication and scanning systems with implemented integration at the system level.The obtained results of research on the integration of communication and scanning means, in particular: the analysis of the performance of generalized ISAC networks and the conclusions about the fundamental limits of performance obtained for a simple structure made it possible to determine the best compromise between the characteristics of scanning and the bandwidth of the communication channel, provided an opportunity to create practical schemes, which approximate a compromise of waveforms, coding tables, structures and protocols.
Keywords: integrated scanning and communication system; radio access network; spectral efficiency; radio frequency scanning; wireless communication; flexible communication system; radar imaging; tomography